Hypertension modifies OPG, RANK, and RANKL expression during the dental socket bone healing process in spontaneously hypertensive rats - Manrique, Natalia [UNESP]; Silva Pereira, Cassiano Costa [UNESP]; Luvizuto, Eloa Rodrigues [UNESP]; Rodriguez Sanchez, Maria Del Pilar [UNESP]; Okamoto, Tetuo; Okamoto, Roberta [UNESP]; Sumida, Doris H. [UNESP]; Antoniali, Cristina [UNESP] (Springer, 2015)
Objective The aim of this study was to evaluate the dental socket bone healing process by histomorphometric and immunohistochemical analysis of osteoprotegerin (OPG), receptor activator of nuclear factor-kappa beta (RANK), and receptor activator of nuclear factor-kappa beta ligand (RANKL) proteins in spontaneously hypertensive rats (SHR).Materials and methods Under general anesthesia, 25 Wistar rats and 25 SHRs underwent upper right incisor extraction. Rats were euthanized after 7, 14, 21, 28, or 42 days of dental extractions. Histomorphometric and immunohistochemical analyses of OPG, RANK, and RANKL proteins were performed.Results Histomorphometric results showed decreased bone healing and reduced bone trabecular thickness in SHRs. Immunohistochemical reactions showed intense RANKL and RANK immunolabeling at 14 and 28 postoperative days and mild OPG immunolabeling at 7, 14, and 21 days after surgery in SHRs.Conclusion The results of this study show that RANK, RANKL, and OPG immunolabeling was altered in SHRs, and these results are associated with bone healing delay and decreased trabecular thickness in SHRs.Clinical relevance Hypertension alters the expression of RANK, RANKL, and OPG and delays the socket bone healing process. These alterations could influence some dental procedures such as orthodontic treatment and implant placement.
Keywords: Extraction socket healing; Histomorphometry; Spontaneously hypertensive rats; OPG; RANK; RANKL